Design System of the High Order Elliptic Gear Pair Pitch Curve based on the SolidWorks - Yan Zhaochao; Guan Dianzhu; Chen Yang; Wei Daishan (Jixie chuandong)
In order to improve the problem of design calculation complex and manufacturing difficulty of non- circular gear pair,taking the high order elliptic non- circular gears as the research object,according to the principle of non- circular gear meshing,the method of calculation and design of the pitch curve of non-circular gear. Taking Solid Works as a development platform,the high order elliptic gears pitch curve design system is developed in the VB 6. 0 environment,the system includes a parameter calculation module,the pitch curve concavity and convexity check calibration module and pressure angle,root cutting,curve plotting module and so on. Finally,by cubic spline curve fitting,the computer aided design of high order elliptic gear pitch curve is realized,and the efficiency and precision of the elliptical gear drive design are improved.